Proposal for the creation of a cafeteria specialized in sweets and traditional drinks from coastline with vanguard techniques - Medina Espinosa, Anamaría Belén; Beltrán Chaug, Denisse Valeria (Ingeniería Química y Desarrollo, 2024)
Dulce Identidad is a food and beverage establishment, having as its main theme the offer of novel products on its main menu that originate from recipes that remain in history and tradition, such as sweets and traditional drinks from the coastal region of Ecuador, presented in a fantastic prospect. With the present project, the aim was for sweets to have much more prominence and to be considered as an offer in a cafeteria. The sweet world has many trails and colors that can be exploited with a little dedication and knowledge. The methodology used is the mixed one for the amount of information to be used that requires different techniques such as surveys and focus groups. Within the project, deconstruction was used together with the signature kitchen trend to rebuild sweets and drinks. The acceptance result that was obtained with the surveys and the tasting within the focus group guarantees a viability with 93% that can be used, among the most outstanding products according to preference were the alfajor with 36%, and the sweet fig and the sponge cake with 16%. The basis of the project is, of course, to provide positive experiences that promote tourism within the city of Guayaquil.
Keywords: Sweets; Traditional drinks and Beverages; Ecuador; Cafeteria; Vanguardism